Teacher’s Profile based on Competences - Álvarez, Margarita María (2011)
Competency-based education holds the potential to become an effective plan aimed at improving the learning of students and, thus preparing students to address future work. However, this approach requires a long process of reforms, which necessarily implies the transformation of the education participants: teachers and students. Since the group of teachers is a fundamental part of competency-based education, this study presents the profile or characteristics necessary in university teachers.